Making it Possible: The Evolution ofRatep — a Community-Based Teacher Education Program for Indigenous Peoples - York, Frank A.; Henderson, Lyn (The Australian Journal of Indigenous Education, 2003)
Abstract Since 1990, the School of Education at James Cook University has produced and delivered a successful offcampus Bachelor of Education for Aboriginal and Torres Strait Islander people in their home communities through the Remote Area Teacher Education Program (RATEP):A community-based teacher education program for Indigenous peoples. This paper examines five key areas. One is the intersystemic management structure that has majority representation from Indigenous communities and peak education bodies as well as representation from the other three stakeholders: Education Queensland, the School of Education at James Cook University and the Tropical North Queensland Institute of Technical and Further Education (TAFE). A second area is RATEP’s innovative use of information and communication technologies in teaching and learning. A third theme is its dynamic evolution from (a) two dedicated RATEP sites in the Torres Strait to 12 sites throughout Queensland; (b) geographically remote sites to a combination of remote, rural, and urban sites; (c) a principle where students gather at a dedicated site with its own teachercoordinator to clusters where a number of students are living in different locations and the coordinator travels between these; (d) movement of sites from location to location depending on need and demand; and (e) a fixed program to a highly flexible one that allows multiple entry and exit points, including honours. A fourth area is the critical insights generated from research into the program by Indigenous and non-Indigenous researchers. The final theme is the retention of graduates from RATEP within the classroom and their promotion into the administrative and advisory teaching sectors.